'The Summers Were Getting Hotter': exploring motivations for migration to Tasmania away from mainland Australia. Issue 4 (2nd October 2022) - Osbaldiston, Nick
ABSTRACT: In recent times there has been a population turnaround in the island state of Tasmania sparked by an increase in in-migration of mainland urban dwellers. This paper argues that one of the major driving factors of this change is the quest for a new lifestyle in regional/rural life, that incorporates a desire for a temperate climate. As literature in lifestyle migration shows, this quest for a new life does not end once migration is over. Rather, the migration experience continues well after the move. In this paper, it will be shown how weather not only attracts migrants into Tasmania, but then encourages/discourages certain activities allowing the individual to engage in new ways of living. The paper suggests that while we need to be careful about romanticising this, we can potentially view this shift as emblematic of people's relationship to climate change.